RMAN recipes for oracle database 12c : a problem-solution approach - Kuhn, Darl; Alapati, Sam; Nanda, Arup (Apress : Imprint: Apress, 2013)
RMAN Recipes for Oracle Database 12c is an example-driven approach to the Oracle database administrator's #1 job responsibility:  Be able to recover the database. Of all the things you are responsible for as database administrator, nothing is more important than the data itself. Like it or not, the fearsome responsibility of protecting your organization's most critical data falls squarely upon your shoulders: Lose that data and your company could fail. Lose that data and you could be out of a job. Oracle's flagship database product fortunately implements a wide-ranging feature set to aid you in the all-important task of safeguarding against data loss. Recovery Manager, or RMAN, is at the heart of that feature set, and is the tool most-often used to initiate database backup and recovery operations. In this book, well-known authors and database experts Darl Kuhn, Sam Alapati, and Arup Nanda have created a set of examples encompassing the gamut of backup and recovery tasks that you might need to perform. Sometimes, especially when the heat is on, a good example is what you need to get started towards a solution. RMAN Recipes for Oracle Database 12c delivers. It'll be the book you reach for when that dreaded call comes in at 3:00am some dreary morning. It'll be the book that lets you sleep at night knowing that no matter what transpires, that you've done your job well and can recover from any outage. RMAN Recipes for Oracle Database 12c gets right to the point with quick and easy-to-read, step-by-step solutions that can help you backup and recover your data with confidence.